Police Barracks, Port of Spain, Trinidad, B.W.I. - (:unkn) unknown (James Book Store, 2010)
External view of a corner of the Police Barracks building, Port of Spain - St. Vincent Street on the left and Sackville Street on the right.
Colour: Green, Red, Orange, Grey, Black and White; Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Police stations--Trinidad and Tobago; Public buildings--Trinidad and Tobago; Architecture--Trinidad and Tobago; Fences--Trinidad and Tobago; Cities and towns--Trinidad and Tobago--Port of Spain; [1920]; Hedges--Trinidad and Tobago; Palms--Trinidad and Tobago